Medical Image Computing and Computer Assisted Intervention - MICCAI 2020 : 23rd International Conference, Lima, Peru, October 4-8, 2020, Proceedings, Part III /: 23rd International Conference, Lima, Peru, October 4-8, 2020, Proceedings, Part III. (2020) - Unknown
No abstract available